Impact of Privatization of the Palestinian Electricity Sector: Case Study - Privatization of the Electricity Sector in Tulkarm City - Sweis, Khaled Mohammed Hasan; Sweis, Ola Jamal; Qariab, Yasmeen Salam; Hamshri, Hadeel Ali; Ghanem, Nahawand Omar; Shalabi, Ola Belal (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed at identifying the effects of privatizing the electricity sector in Tulkarm city. The analytical descriptive method was used, and the data were collected using a questionnaire. The population of the study covered eight sectors, and 350 questionnaires were used for the sake of investigating this issue. The SPSS was employed in processing the data and testing the hypotheses. The findings were as the following: privatizing the electricity in Tulkarm will improve the monthly collection of money and it will also result in a more efficient system in this field. The researcher recommended that privatizing this sector should be conditioned and well-studied so that it will not raise the burden on consumers. Furthermore, the researchers recommended that there should be a real partnership between the Municipality of Tulkarm and the private sector, which guarantees task distribution to boost efficiency and performance.